Single Piles and Pile Groups Capacity in Unsaturated Sandy Clay Based on Laboratory Test - Pujiastuti, Heni (Universiti Teknologi Malaysia, 2022)
Pile capacity is one of the controlling factors in the foundation design. In this study, compression and tension tests were carried out on model piles driven in sandy clay in a test box. The diameter of concrete single-pile models was 16 mm, with ratios of 6, 10, 15 and 20 for pile length (L) to diameter (d). The diameter and length of concrete pile group models were 10 mm and 200 mm, respectively, with four different configuration groups, i.e., single pile, two piles (2×1), three piles (triangle), and four piles (2×2). The sandy clay was prepared in three different water contents of 17.40, 23.44, and 27.86. The capacities of the single piles and pile groups subjected to uplift load were smaller than those under compressive load. Increasing the pile length to the ratio of diameter (L/d) and matric suction resulted in increased capacity of single piles subject to uplifting and compressive loads. The pile groups' capacity depended on both the matric suction and the pile number in a group. The pile groups' compressive capacity in a condition of unsaturated soil (with the matric suction of soil of 73.67 kPa) increased by 294.96-346.39 when compared to those in saturated soil conditions (with the matric suction of soil of 2.727 kPa). © 2022 Penerbit UTM Press. All rights reserved.